Schule am Ende der Buchkultur Medientheoretische Begründungen schulischer Bildungsarchitekturen - Böhme, Jeanette (Verlag Julius Klinkhardt, 2006)
At the end of the book culture, enquiries about the self-understanding of school expand in the recognisable horizon of a transmedial network culture. Media-critical reform pedagogy holds on to talk and action as the leading medium and conceives school as a "media-resistant polis". In contrast, the mainstream school is justified as a 'literary counterculture' in which writing is to be defended as the highest achievement in the process of civilisation. In both lines of discourse on school pedagogy, school is conceived as a monomedial province. With reference to this, the present volume asserts: In mono-medial school provinces, which orient educational processes to a dominant leading medium, competences for a meaning-generating examination of topics, questions and problems of the establishing network culture are only marginally developed. Schools designed in this way are also less and less successful in connecting to the experiential horizons of children and young people who roam the extracurricular spectrum of media cultural architectures as transmedial nomads. Accordingly - also in view of the PISA results - the thesis of a new variant of school alienation must be examined. In critical distance to the perspectives presented, the potentiality of a media-ecological approach for a theorisation of school as a media-specific educational architecture is demonstrated. In doing so, the impact of media technologies on the contrasting shaping of spatiotemporal relations of cultural orders as well as synaesthetic relations of modes of perception will be examined. In relation to this, new educational potentials of transmedial networks can be heuristically identified. These are the focus of both the programmatic perspectives of media-ecological educational research and the conceptual outlook on schools in the image of a 'hypermedial plateau network'. (DIPF/Orig.)